IMPROVING THE IMPLEMENTATION OF GOOGLE MEET TO IMPROVE THE ASPECT AND THE COMPONENT OF SPEAKING SKILL ON THE STUDENTS FROM NON ENGLISH SPEAKING BACKGROUND - mutakhirani mustafa; Natalia Manuhutu; Fransiska Densiana Luruk (English Tadris Department, Faculty of Tarbiyah and Teacher Training, State Islamic University (UIN) Datokarama Palu, 2021)
The purpose of this study is to investigate how the use of google meet can improve the speaking ability of students of iain Intensive English 1 program Syekh Nurjati Cirebon. This particular research is categorized as action research. These actions are performed in three cycles based on the class schedule. The study involved 35 students. This research data is qualitative and quantitative data. Qualitative data is obtained by observing the teaching and learning process in speaking classes. Meanwhile, quantitative data is obtained through tests, and questionnaires. The findings suggest that the use of Google Meet terbukti meningkatkan keterampilan berbicara mahasiswa. Therefore google meet is very suitable to be used as online or virtual learning especially in improving students' speaking skills that focus on aspects and components of student speaking skills, but there are some drawbacks that can make learning less effective and less efficient when used as a particular application in the learning and teaching process. Therefore, all educators who use application media such as google meet are able to master and professional in using the application. Hopefully this pandemic ends quickly and we can adjust how the future of education around the world goes forward. For the next researcher, can be focused on the influence of the implementation of google meet application in speaking subjects to the interest of students to improve speaking. Based on this study, researchers found students' enthusiasm is very high in learning to speak, this proves that the google meet application can improve aspects and components of student speaking because it is influenced by increased student motivation during the use of google meet application compared to other applications.